2017
DOI: 10.1080/09593985.2017.1318419
|View full text |Cite
|
Sign up to set email alerts
|

Intra-rater and inter-rater reliability of the standardized ultrasound protocol for assessing subacromial structures

Abstract: The reliability of the current standardized protocol for US examination of SI was excellent and considered feasible for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 49 publications
2
28
1
Order By: Relevance
“…Some studies have found significant differences in TT between symptomatic and non-symptomatic participants, 29 30 which are in contrast with the current study and a recent study. 18 The reason for the discrepancy across studies may be due to the use of different methods for measuring TT, small sample sizes, different inclusion criteria or, as in this study, the inclusion of more active controls (recruited among health personnel) with potentially thicker tendons than the average population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Some studies have found significant differences in TT between symptomatic and non-symptomatic participants, 29 30 which are in contrast with the current study and a recent study. 18 The reason for the discrepancy across studies may be due to the use of different methods for measuring TT, small sample sizes, different inclusion criteria or, as in this study, the inclusion of more active controls (recruited among health personnel) with potentially thicker tendons than the average population.…”
Section: Discussionmentioning
confidence: 86%
“…Excellent reliability, and MDC of ≤0.33 mm, indicates that the variable is sensitive for detecting changes, in line with a previous study using the same method for measuring TT. 18 This means that it may be a clinically relevant measurement for assessment of changes in tendon properties, such as increased/decreased oedema. Some studies have found significant differences in TT between symptomatic and non-symptomatic participants, 29 30 which are in contrast with the current study and a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…This may be directly proportional to SMT exposure. Different authors used this positioning technique for the SMT examination [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound images are captured with the patients seated in an upright position, feet flat on the floor, neutral trunk posture, and head facing forward. For the SST thickness measure the patient has the hand on the affected side on the ipsilateral posterior hip with the humerus in extension and the tendon is measured in a longitudinal [72] and a transverse view [67]. AHD is measured in the neutral position (arm resting at the side) and respectively with 45° and 60° of active shoulder elevation in the scapular plane [72, 73].…”
Section: Methodsmentioning
confidence: 99%
“…For the SST thickness measure the patient has the hand on the affected side on the ipsilateral posterior hip with the humerus in extension and the tendon is measured in a longitudinal [72] and a transverse view [67]. AHD is measured in the neutral position (arm resting at the side) and respectively with 45° and 60° of active shoulder elevation in the scapular plane [72, 73]. SST neovascularity assessed by power Doppler is measured with the shoulder internally rotated with the dorsal side of the hand placed on the sacrum, and the elbow flexed and directed laterally [74].…”
Section: Methodsmentioning
confidence: 99%